The effect of mengkudu fruit methanolic extract and methanolic residual fraction on GLUT-4 protein elevation - Aguslina Kirtishanti; Ryanto Budiono (Indonesian Journal of Pharmacy, 2009)
Investigating in the Diabetes Mellitus drug which one having good activity and tolerance to patients are still in researchers’ concern. One of the main topics now days is the use of mengkudu plants as a traditional medicine of Diabetes Mellitus. This research was aimed to determine the increase of GLUT-4 protein in type 2 Diabetes Mellitus rats after given methanolic extract and methanolic residual of mengkudu fruit. The male rats were diabetic induced with exogenous i.p. insulin for 10 days. After showing hyperglycemic effect, the rats were given orally methanolic extract and methanolic residual fraction of mengkudu fruit for 4 days. On the fifth day, fasting blood glucose was measured and the rats were sacrificed to take the thigh muscle tissue for immunohistochemical calculation. The result showed that methanolic extract and methanolic residual of mengkudu fruit increase the amount of GLUT-4 protein, but can not reduce fasting blood glucose levels of male white rats.Key words : mengkudu fruit (Morinda citrifolia L.), methanolic extract and methanolic residual, type 2 Diabetes Mellitus, GLUT-4 protein